PERANCANGAN SISTEM INFORMASI ADMINISTRASI KEPENDUDUKAN DESA BERBASIS FRAMEWORK ITIL: STUDI KASUS DESA TINGKOHUBU TIMUR - Zain Ahmad Didath; Adam, Moh. Gibran; Katili, Said (STMIK BINA PATRIA, 2026)
Village public services, particularly administrative management and population data recording, are still handled manually in many villages, resulting in slow processing, difficulty retrieving archived documents, and a risk of data loss. This condition is also found in Desa Tingkohubu Timur, Gorontalo, where population data management remains fragmented and correspondence services are still entirely manual. This study designs a Village Population Administration Information System (SIAKDes) to digitalize these services and improve service quality. A qualitative approach was adopted, combining interviews and direct observation with village officials. The system was developed using the Waterfall method, while service management was structured around the ITIL (Information Technology Infrastructure Library) Service Lifecycle, covering Service Strategy, Service Design, Service Transition, Service Operation, and Continual Service Improvement. Unlike prior studies that apply ITIL only to isolated phases, this research integrates all five phases with a decile-based community classification mechanism for social-assistance targeting, an aspect not yet addressed comprehensively in the village information-system literature. The resulting system provides population data management, correspondence services, birth and death record management, and decile-based classification of social assistance recipients. Usability testing yielded a System Usability Scale (SUS) score of 77.5 (Acceptable, Grade B), confirming that SIAKDes is feasible and easy to operate for improving administrative efficiency and accuracy in Desa Tingkohubu Timur. Keywords Village Information System, Population Administration, ITIL, Waterfall, Public Service